STUDI AWAL GAMBARAN PENGETAHUAN DASAR DAN SIKAP WISATAWAN BACKPACKER MANCANEGARA DI BALI MENGENAI RESIKO INFEKSI RABIES - I Gede Eddy Pramana Agustina; Losen Adnyana (Universitas Udayana, 2015)
OVERVIEW BASIC KNOWLEGDE AND ATTIDUDE FOREIGN BACKPACKER REGARDING RABIES RISK INFECTION: PREELIMINARY STUDYSince Bali establish as rabies endemic area in 2008, all people in Bali have high risk for getting rabies infection, those are include foreign tourists who come to Bali. Backpacker is one who has high risk of infection because of their habitation of getting their destination on foot and travelling with limitingbudget. This study describes the basic knowledge and attitude of foreign backpacker regarding rabies infection prevention with deep interview based on preprintedquestioners.This study uses cross sectional design held on December 2013to February 2014 with 56 samples. We get 92,8% foreign backpacker who travelling in Bali do not know that Bali is a rabies endemic area, 82,1% foreign backpacker who travelling in Bali do not know how to avoid rabies infection, 7,1% foreign backpacker who travelling in Bali do not know dog as main carrier rabies in Bali, 64,3% foreign backpacker who travelling in Bali did not get information regarding rabies risk, initial management of biting before trip and 92,9% foreign backpacker who travelling in Bali did not receive complete rabies vaccine shot before travelling in their country.